Penerapan Kepemimpinan Kolaboratif Kepala Sekolah Guna Membangun Tim Kerja yang Solid di SD SWASTA ARISA MEDAN DELI - Annisa Arnun (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
Nowadays, education is a challenge that cannot be avoided by any organization, including schools. One of the schools facing this challenge is SD Swasta Arisa Medan Deli. In addition to maintaining its existence, the school must also revolutionize the view of leadership styles that are aligned with the goals of national education as well as building a solid team of teachers, in harmony, in harmony, and in the same direction. Facing these challenges requires a lot of thought and intervention from all solid aspects. A leadership model that expands the mix of personnel in the school is the key to building a solid team of teachers. Thus, this study intends to explain the collaboration leadership skills in building a solid team that can meet the expectations of the community. This study uses a qualitative approach with a literature method. The collaborative leadership style of the school principal refers to the leadership model needed by the school in building solid teamwork.